THE EFFECT OF FARMER CHARACTERISTICS ON PERCEPTIONS OF THE FERMENTED COCOA BEANS TECHNOLOGY IN BENGKAYANG REGENCY, WEST KALIMANTAN. - Maswadi Maswadi; Shenny Oktoriana; Anita Suharyani (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
Cocoa Commodities, especially cocoa beans, have a great opportunity to be developed due to high market demand, this must be in line with the good quality of cocoa beans owned with the world market demand standards which means that at the farm level the cocoa farming must implement the Good Agricultural Practices (GAP) and Good Handling Practice (GHP). This study aims to determine the effect of the characteristics of cocoa farmers on farmers' perceptions of fermented cocoa beans. The method used in this study is the survey method. The research location is Sui Duri Village, Sui Raya District, Bengkayang Regency. Data analysis using logit regression. The results showed that the five characteristics of the farmers, namely age, education, land area, number of family dependents and farming experience had a positive influence on farmers' perceptions, this indicates that farmers' characteristics are very important on the farmers' decision to adopt cocoa bean fermentation technology.Keywords: Characteristics of farmers, cocoa, perceptions, Good Agricultural Practices (GAP), Good Handling Practices (GHP)